2022
DOI: 10.3892/ijmm.2022.5109
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of wogonin following traumatic brain injury by reducing oxidative stress and apoptosis via the PI3K/Nrf2/HO‑1 pathway

Abstract: Traumatic brain injury (TBI) is usually caused by accidental injuries and traffic accidents, with a very high mortality rate. Treatment and management following TBI are essential to reduce patient injury and help improve long-term prognosis. Wogonin is a flavonoid compound with an antioxidant effect extracted from Scutellaria baicalensis Georgi. However, the function and mechanism of wogonin in protecting brain injury remain to be elucidated. The present study established a TBI model of Sprague-dawley rats and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…16,19,32,33 Wogonin is a natural polyphenolic flavonoid and exhibits various remedial effects, including anti-inflammatory, antioxidative, and anticancer effects. [7][8][9][10] Studies have yet to comprehensively investigate the proinflammatory responses and the related mechanism in BisGMA-treated macrophages incubated with wogonin. 16 In this study, we investigated the inhibitory effects of wogonin on BisGMA-induced cytotoxicity and genotoxicity in macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,19,32,33 Wogonin is a natural polyphenolic flavonoid and exhibits various remedial effects, including anti-inflammatory, antioxidative, and anticancer effects. [7][8][9][10] Studies have yet to comprehensively investigate the proinflammatory responses and the related mechanism in BisGMA-treated macrophages incubated with wogonin. 16 In this study, we investigated the inhibitory effects of wogonin on BisGMA-induced cytotoxicity and genotoxicity in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Wogonin is a natural dihydroxyl flavonoid extracted from plants of the Scutellaria and Andrographis species of the Lamiaceae family 6 . Wogonin has been demonstrated to exhibit anti‐inflammatory, antiallergic, anticancer, and antioxidative properties 7–10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the key components of JCD are associated with neural apoptosis, and many of them also involve changes in AKT protein. For example, wogonin, a key component of JCD identified in this paper, can prevent hippocampal injury after brain trauma through antioxidation and anti-apoptosis, which has been shown to occur through the PI3K/Akt/nuclear factor E2-related factor 2 (Nrf2)/HO-1 pathway[ 38 ]. Baicalein reduces sevoflurane-induced neurodegeneration, improves learning and memory retention in rats, and modulates the PI3/Akt/GSK-3β and JNK/ERK signaling pathways[ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wogonin is an important flavonoid, isolated from the root of Scutellaria baicalensis Georgi ( Chirumbolo, 2013 ) . It has many pharmacological effects, including antioxidant and anti-inflammatory ( Zheng et al, 2020 ; Feng et al, 2022 ; Shao et al, 2022 ). Fang et al found that wogonin can inhibit IL-1β-induced inflammatory response and extracellular matrix degradation in NP cells ( Fang et al, 2018 ).…”
Section: Phytochemicals For the Treatment Of Idd By Targeting Inflamm...mentioning
confidence: 99%